Kalam Allah: Tumpuan Terhadap Penghujahan al-Qadi ’Abd al-Jabbar - Ibrahim, Mohd Radhi (Afkar: Jurnal Akidah dan Pemikiran Islam, 2000)
The aim of this article is to examine the polemic between Islamic Theologians regarding the speech of God, with special attention to al-Qadi ’Abd al-Jabbar’s arguments.